2011
DOI: 10.2527/jas.2010-3013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physically effective fiber on chewing activity, ruminal fermentation, and digestibility in goats1

Abstract: The objective of this study was to evaluate the effects of physically effective NDF (peNDF) in goat diets containing alfalfa hay as the sole forage source on feed intake, chewing activity, ruminal fermentation, and nutrient digestibility. Four rumen-fistulated goats were fed different proportions of chopped and ground alfalfa hay in a 4 × 4 Latin square design. Diets were chemically similar but varied in peNDF content: low, moderate low, moderate high, and high. Dietary peNDF content was determined using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 37 publications
3
41
0
4
Order By: Relevance
“…Similar results have been reported by Asadi et al (2009) and Zhao et al (2011). Numerical differences indicate a lower acetate/propionate ratio in diets with a smaller particle size.…”
Section: Ruminal Parameterssupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results have been reported by Asadi et al (2009) and Zhao et al (2011). Numerical differences indicate a lower acetate/propionate ratio in diets with a smaller particle size.…”
Section: Ruminal Parameterssupporting
confidence: 81%
“…Numerical differences indicate a lower acetate/propionate ratio in diets with a smaller particle size. Thus, working with goats, Zhao et al (2011) concluded that diets high in physically effective fiber tend to increase the molar ratio of propionate and decrease that of butyrate. Le Liboux et al (1999) found that diets consisting of whole dehydrated alfalfa pellets, as opposed to chopped alfalfa, reduce the molar ratio of acetate and increase that of propionate and valerate in cattle.…”
Section: Ruminal Parametersmentioning
confidence: 99%
“…However, the effect of forage on rumen pH depends, to a great extent, on forage particle size, this being particularly small in concentrate pellet-based diets, where the barley straw is almost ground. As a result, using pelleted diets may have no positive effects on rumen physiology, the consequences for animal health being even more detrimental than those from the traditional feeding system due to a decrease in physically effective fibre contents (Zhao et al, 2011). So far, the best strategy to promote optimal rumen fermentation is the use of forage-based rations, although it is known that the feed-togain ratio and average daily gain may be worsened as compared with concentrate-based rations (Carrasco et al, 2009b;Tufarelli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The digestibility of NFC was 78.83±3.61%, which is below the 82.96±9.82% obtained by Branco et al (2010); this digestibility might have been a result of the lower quality of the forage utilised in this study. The increase in the proportion of cell wall (NDF) in the diets leads to decreased digestibility, except for the fiber, which is usually increased due to the greater activity of the cellulolytic bacteria in the rumen Zhao et al, 2011). This did not occur in this experiment; instead, the NDFD and ADFD decreased when the babassu palm hay was added to the diet as a result of the high lignification of the cell wall (Garcez et al, 2014).…”
Section: Resultsmentioning
confidence: 86%